Development of genomic markers for monitoring and research on plethodontid salamanders - Benjamin M. Fitzpatrick; Kara S. Jones; Aaron W. Aunins; Michael S. Eackles; David C. Kazyak (PLoS ONE, 2025)
Despite the importance of plethodontid salamanders and their vulnerability to ongoing environmental change, they are inherently difficult to monitor due to their cryptic nature. Recent advances in genomics have created new opportunities for monitoring of populations and their responses to environmental perturbations. In this study, we developed a new target capture-based genomic panel for the purposes of genetic monitoring in plethodontid salamanders. We demonstrate its utility in several distantly related species and present an example application in two representative species with co-occurring distributions but different ecological attributes and expected patterns of population structure: Plethodon jordani and Desmognathus wrighti . Although the number of successfully assembled loci declined with phylogenetic distance from the original reference species ( Desmognathus spp), we obtained high-quality data from thousands of loci from species in all four genera tested ( Desmognathus , Plethodon , Eurycea , and Gyrinophilus ), which span the deepest split in Plethodontidae. Landscape genetic analyses detected weak but statistically significant geographic structure in P. jordani , and much stronger geographic structure in D. wrighti , as expected based on the lower population density and likely lower dispersal ability of D. wrighti . Our target capture panel is broadly applicable across salamanders in Plethodontidae and has the potential to provide data for a wide range of phylogenetic, biogeographic, and population genetics research questions.